Evaluation of Copper Leaching for Subsequent Recovery from the Waste Dumps of the Linares Mining District and Their Use for Construction Materials - Terrones Saeta, Juan María; Suárez Macías, Jorge; Castañón García, Ana María; Corpas Iglesias, Francisco Antonio (MDPI, 2024)
The development of the population¿s well-being involves the use of different raw materials. However, metallic elements such as copper are currently scarce due to their intensive use in different sectors. Therefore, new sources of raw materials that provide these elements, are of lower cost, and use waste for their extraction must be sought. For this reason, in this research, different waste dumps of the mining district of Linares (Spain) are studied to evaluate the existence of recoverable copper by hydrometallurgical techniques. The material from the waste dump selected as potentially viable is leached with different sulfuric acid solutions (0.25, 0.5, 1, and 2 mol) and at different times, obtaining copper concentrations usable for subsequent hydrometallurgical processes. In addition, in order to develop an environmental hydrometallurgy, the leach waste is characterized, and bituminous mixtures are made with it. The results of the present investigation showed that it was possible to recover 80% of the copper in the waste dumps of the Linares mining district with 1 and 2 mol solutions of sulfuric acid. At the same time, the waste from the leaching process was found to be suitable for use as an aggregate in bituminous mixtures. Therefore, bituminous mixtures were conformed, and it was obtained that the optimum percentage of bituminous emulsion was 6.95% for the proposed granulometry. This emulsion percentage, which corresponds to a residual bitumen percentage of 4.17%, showed particle loss test results of 14% and 18% after immersion. In addition, the stability test values for the Marshall test with the above-mentioned bitumen emulsion percentage and leaching waste showed a stability of 8.99 KN. This fact demonstrates the quality of the bituminous mixture made with the leaching waste for use in bituminous mixtures. Consequently, it can be affirmed that in the present investigation, a significant percentage of copper has been extracted from the waste dumps of the mining district of Linares (Spain) and that the waste after processing can be used in bituminous mixtures, there being a closed cycle of materials in which no waste is produced
Keywords: hydrometallurgy; metallic elements recovery; mining waste; bituminous mixture; circular economy; sustainability; construction materials